2009
DOI: 10.1177/0255761409102322
|View full text |Cite
|
Sign up to set email alerts
|

The use of gestural modes to enhance expressive conducting at all levels of entering behavior through the use of illustrators, affect displays and regulators

Abstract: In this article, I discuss the use of illustrators, affect displays and regulators, which I consider to be non-verbal communication categories through which conductors can employ a more varied approach to body use, gesture and non-verbal communication. These categories employ the use of a conductor's hands and arms, face, eyes and body in a way that is currently being missed by many conducting programs. By utilizing three gestural modes, declamatory, corrective and narrative, conductors have a framework to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The research on body language in music has focused mainly on expressive movements in performance and how these help to communicate the intended emotions to the audience (Davidson, 2007;Davidson & Correia, 2002). Non-verbal communication through the use of facial expressions, eye contact and hand gestures are of special importance in conducting (Mathers, 2009), where direct body orientation and eye contact indicate interest. Also in conducting Jones (1996) found that visual impressions had an effect on the ratings of tone quality, intonation, rhythm, balance, blend, technique, diction, interpretation and musicianship in choral singing.…”
Section: Music Performancementioning
confidence: 99%
“…The research on body language in music has focused mainly on expressive movements in performance and how these help to communicate the intended emotions to the audience (Davidson, 2007;Davidson & Correia, 2002). Non-verbal communication through the use of facial expressions, eye contact and hand gestures are of special importance in conducting (Mathers, 2009), where direct body orientation and eye contact indicate interest. Also in conducting Jones (1996) found that visual impressions had an effect on the ratings of tone quality, intonation, rhythm, balance, blend, technique, diction, interpretation and musicianship in choral singing.…”
Section: Music Performancementioning
confidence: 99%
“…However, in the new factor structure (Phase 2), it seems that what underlies is a vision of expressive body language achieved through the conjunction of the whole body, whether the left arm, facial expression or eye contact. It might be that self-observation has allowed participants to gain a holistic view of body movements and to become aware that not only the movement of the left arm contributes to an expressive and poetic conducting, but that the whole body must be harmoniously integrated into producing the desired expressive effect (Johnson et al, 2003; Mathers, 2009). This points to a maturation in the conception of the expressive function of the gesture from a unitary vision of the human body and body language and coincides with the idea of Johnston (1993) that gestural activity can be separated into concrete skills, but its effectiveness can only be examined by understanding the body as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomous use of the left arm is also emphasized, as is interruption of movement and cuts, as well as general body attitude and facial expressiveness (including eye contact), and the plasticity of gesture according to the sound to be transmitted. All these technical gestures have been approached by different authors and researchers from different points of view (see Bodnar, 2013; Bonshor, 2017; Chaffin, 2011; Colson, 2012; Green, 1987; Johnson, Fredrickson, Achey, & Gentry, 2003; Lorenzo de Reizabal & Benito, 2018; Mathers, 2009; Silvey, 2013; Silvey & Major, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding nonverbal communication has enormous implications on the practice of conducting. Mathers (2009) explained that the declamatory mode, corrective mode, and narrative mode are three types of nonverbal communication. The conductor uses the corrective mode (i.e., the beat pattern) to solve problems.…”
Section: Gesture: Movement With Meaning For Conductors and Singersmentioning
confidence: 99%
“…The declamatory mode and the narrative mode of nonverbal communication serve more expressive purposes, with the declamatory mode emphasizing illustrators and affect displays and the narrative mode being accessed by regulators and affect displays. Many conductors surveyed expressed discomfort with using gestures in the declamatory and narrative modes (Mathers, 2009). Van Weelden (2002) urged conductors to be aware of nonverbal behaviors while in front of an ensemble.…”
Section: Gesture: Movement With Meaning For Conductors and Singersmentioning
confidence: 99%